2012
DOI: 10.1186/1472-6831-12-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk indicators of gingivitis and periodontitis in a Multi-Centre study in North Jordan: a cross sectional study

Abstract: BackgroundThere are limited data about the epidemiology and risk factors/indicators of gingivitis, aggressive periodontitis (AgP) and chronic periodontitis (CP) in Jordan. The aim of this study was to assess the prevalence and risk indicators of gingivitis, AgP and CP.MethodsA sample of 595 subjects was randomly selected from subjects escorting out-patients attending a Medical Center, a Dental Teaching Hospital, and 2 private dental clinics. The socio-demographic variables, oral hygiene habits, income, smoking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
82
4
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(109 citation statements)
references
References 34 publications
18
82
4
5
Order By: Relevance
“…By comparison with the existing research, other studies in Australia21, 22 and internationally23, 24 are largely cross‐sectional or, if prospective, involve older children8. Contextual factors in developing countries reduce ability to compare the caries experience of these children with other published work25.…”
Section: Discussionmentioning
confidence: 99%
“…By comparison with the existing research, other studies in Australia21, 22 and internationally23, 24 are largely cross‐sectional or, if prospective, involve older children8. Contextual factors in developing countries reduce ability to compare the caries experience of these children with other published work25.…”
Section: Discussionmentioning
confidence: 99%
“…Periodontal disease is one of the most common chronic diseases affecting approximately half of US adults aged 30 and older [5]. In Jordan, among young adults with mean age 28 years old, 76% had gingivitis, 2.2% had aggressive periodontitis and 5.5% had chronic periodontitis [6].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 7.2% pregnant women had complaints of the Temporomandibular joint (ΤΜJ) and myofascial pain. [58] Some other authors made similar observations, reporting a prevalence of gingivitis was 86.2% & 97.0% [59,60] Meanwhile, some cross-sectional research demonstrated that the percentage of pregnant women with gingivitis was 89.0% in Ghаnа, 86.2% in Τhаilаnd, & 47% in Ɓrazil. [35,61] Among the pregnant women examined, 62.0% presented with moderate gingival inflammation, & 64.0% presented with at least some plaque.…”
Section: Discussionmentioning
confidence: 54%